Obstruction at the level of foramen of monro causing obstructive hydrocephalus - Kashyap, Dushyant; Chug, Ashish; Punia, Prashant; Gotecha, Sarang; Ranade, Deepak; More, Bhagirath; Chhabra, Shobhit; Raghu, Vybhav (International Surgery Journal, 2021)
Background: The foramen of monro is also known by the name of interventricular foramen. The study was conducted to determine the etiology, clinical picture, radiological features, and different modalities of management and related complications. Methods: A prospective study of 30 cases with diagnosis of hydrocephalus due to obstruction at the interventricular foramen. Lesions at the foramen of monro were addressed either by open craniotomy approach or neuroendoscopy approach. For open craniotomy transcortical or interhemispheric approach was preferred and Karl Storz’s LOTTA system was used for all the neuroendoscopic procedures. Results: Craniopharyngioma and colloid cysts were the most common pathology in children and adults respectively. Endoscopic approach was particularly helpful in decreasing the convalescence period and postoperative complications. Wound site CSF leak is the most commonly faced complications. In our study, out of 30 patients, males accounted for 23 (77%) cases and females for 7 (23%) cases. Majority were in the age group of 20-40 years. The most common presenting complaints of patients having foramen of monro obstruction with hydrocephalus were headache and vomiting. Gadolinium enhanced contrast MRI of brain was the investigation of choice for diagnosing these lesions. Conclusions: Endoscopic approach can be offered as a first line of treatment as a part of standard treatment in all patients having foramen of monro obstruction. It obviates the need for multiple shunt procedures. Although small solid lesions less than 3 cm in size can be addressed by endoscopic approach, the learning curve required for endoscopic approach to deal with solid lesions is very steep.